Linguistic Style and Cognitive Load in Distance Learning: A Discourse Analysis of Sociolinguistics Modules - Rasyki, Adrian (Jurnal Bahasa dan Sastra, 2026)
Although Cognitive Load Theory (CLT) is widely used to evaluate multimedia learning, its application to textual language styles in printed distance learning modules remains under-explored. To address this gap, this study investigates how specific linguistic choices impact students' cognitive load within Sociolinguistics modules at Universitas Terbuka. Employing a multi-method qualitative design, the research analyzed 40 thematic textual segments and conducted semi-structured interviews with three Indonesian English as a Foreign Language (EFL) students whose first language is Indonesian. The findings indicate that within this specific context, extraneous cognitive load is primarily triggered by dense academic registers, syntactic opacity, and culturally distant examples. Conversely, localized contexts and conversational markers functioned as germane load triggers. These results suggest the presence of an "expert blind spot," where markers of academic rigor paradoxically act as cognitive barriers for autonomous learners. Consequently, instructional designs in text-driven distance education should integrate culturally relevant schemas and explicit linguistic scaffolding to optimize comprehension without diluting theoretical depth.